Success Rate in Patients with Atrioventricular Nodular Re-Entrant Tachycarida (AVNRT) Slow Pathway Catheter Ablation with and without Junctional Rythym - Salman Ahmad, Zahoor Ahmad Khan, Ikram Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: For successful radiofrequency ablation of atrioventricular nodal reentrant tachycardia (AVNRT), slow-pathway radiofrequency catheter ablation leads to junctional rhythm (JR) is now being considered as a very sensitive substitute end goal. During AVNRT RF ablation, a favorable result could be predicted based on the pattern of JR produced. Patients and Methods: This cross-sectional study was conducted on 64 patients presenting with symptomatic AVNRT and undergoing slow-pathway RF ablation in the Department of Cardiology, Hayatabad Medical Complex, Peshawar for the duration from January 2022 to June 2022. RF ablation of slow pathway was performed using a combined anatomical and electrogram mapping approach. Ablation was performed by controlling the temperature and delivering energy over 60 seconds at 60°C. In order to determine if the developed JR was successful, isoproterenol infusion was performed after every ablation pulse. Four different patterns of AVNRT inducibility were considered: intermittent, continuous, sparse, and transient. Position, pattern, and number of junctional beats were used to assess the success rate of ablation. SPSS version 28 was used for descriptive statistics. Results: Of the total patients, there were 36 (56.2%) women and 28 (43.8%) men. The overall mean age was 38.64 ± 18.36 years with an age range 16-80 years. The most prevalent symptom during AVNRT was palpitation found in 41 (64.1%) cases. The prevalence of pre-syncope, dyspnea, and syncope was 3.8%, 3.8%, and 3.4% respectively. The incidence of more than one symptoms were found in 21 (32.8%) patients. Almost all the patients displayed antegrade AH jumps and indicated dual AV nodal conduction. Out of total 156 RF, it took 114 (73.1%) RF energy applications to successfully ablate 38 (59.4%) patients with loss of AVNRT inducibility. About 126 (80.8%) patients developed JR with given specificity 42.6%, sensitivity 89.6%, and negative predictive value 61.8%. Conclusion: The present study found that the JR predicts the success of AVNRT RF ablation at a high level of sensitivity, but not to a specific degree. However, the findings indicate that its specificity may rise with the appearance of > 14 total tight junctions beats. Furthermore, if the forecast of effective slow-route RF ablation in relation to the existence of JR remains not consistent adequate, its absence might be a trustworthy marker of the pathway needing greater energy application delivery to be abolished. Keywords: Atrioventricular nodular re-entrant tachycardia (AVNRT), Slow pathway catheter ablation, Junctional rhythm, success rate